Penegakan Hukum Terhadap Tindak Pidana Korupsi Politik dalam Proses Penganggaran APBD di Pemerintahan Daerah - Ni Kadek Marsya Gayatri Arthania; Ni Komang Febrinayanti Dantes; Ni Ketut Sari Adnyani; Gusti Ayu Apsari Hadi; I Gusti Ngurah Budiyasa (Jurnal Ilmu Hukum Sui Generis, 2026)
This article discusses law enforcement against political corruption in the budgeting process of the Regional Budget (APBD) within the local government. The research uses normative legal methods with statutory, conceptual, and case study approaches. Political corruption in APBD budgeting is not only in the form of bribes or gratuities, but also involves project manipulation and the use of budgets for political interests, which has direct implications for regional financial integrity and public services. Law enforcement against this practice is regulated in various regulations, including Law Number 31 Year 1999 jo. Law No. 20/2001 on the Eradication of Corruption as well as the Law on Local Government and technical regulations related to local financial management. Despite the availability of adequate legal instruments, in practice, enforcement is often hampered by weak proof of quid pro quo elements, political intervention, limited capacity of investigators in the regions, and low protection for whistleblowers. This article emphasizes the need for a more strategic and integrated approach to law enforcement, including strengthening synergies between law enforcement agencies, reforming internal control systems, digitizing budget processes, and the active role of civil society and the media as external watchdogs. Legal effectiveness in cracking down on political corruption can only be achieved through strong institutional commitment, political courage, and critical public participation in transparent and accountable local financial governance